Disaster Psychiatry: Mental Health Implications and Early Psychosocial Interventions Following Disasters - Usta Sağlam, N. Gamze; Uçar Bostan, Büşra (Cerrahpaşa Medical Journal, 2023)
Psychiatrists have a substantial preventative role in assisting the recovery process of the individual and society in the aftermath of a disaster. The majority of the psychiatric reactions after disasters are self-limiting and can be considered “normal reactions to an abnormal event.” However, the persistence of symptoms may impair functionality and lead to a psychiatric disorder. The identification of populations at risk from the effects of the trauma will help indicate who may require additional intervention in the future. The principles of psychological first aid alleviate the effect of the trauma by creating an environment of security, hope, connectedness, and self-efficacy. Healthcare workers directly involved in helping people exposed to traumatic events may experience traumatic stress themselves. This article discusses early psychosocial interventions in the aftermath of a disaster along with the psychosocial concerns for healthcare workers. Ethical and proper use of media which is a vital part of disaster and crisis management is emphasized. Cite this article as: Usta Sağlam NG, Uçar Bostan B. Disaster psychiatry: Mental health implications and early psychosocial interventions following disasters. Cerrahpaşa Med J 2023;47(S1):89-92.